2021
DOI: 10.1007/s11606-020-06578-4
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization and Post-hospitalization Outcomes Among Teaching Internal Medicine, Employed Hospitalist, and Locum Tenens Hospitalist Services in a Tertiary Center: a Prospective Cohort Study

Abstract: BACKGROUND: There are no prospective studies comparing hospitalization and post-hospitalization outcomes between teaching internal medicine services and nonteaching hospitalists, and no prospective studies comparing these outcomes between locum and employed hospitalists. OBJECTIVE: To compare the length of stay, hospital costs readmission rate, and mortality rate in patients treated by teaching internal medicine services vs. hospitalists and among patients treated by locum vs. employed hospitalists. DESIGN: Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Another study comparing locum and permanent doctors found locum doctors had shorter stays and lower treatment costs but there were no differences in mortality or readmissions [38].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Another study comparing locum and permanent doctors found locum doctors had shorter stays and lower treatment costs but there were no differences in mortality or readmissions [38].…”
Section: Discussionmentioning
confidence: 96%
“…A US study investigating the impact of locum working on patient outcomes, including mortality, 30-day hospital readmissions and cost of care found significant differences in mortality rates for patients who were treated by locums who had worked for less than 60 days in the organisation but no significant differences for patients who were treated by locums who had worked in the organisation for 60 days or more [ 7 ]. Another study comparing locum and permanent doctors found locum doctors had shorter stays and lower treatment costs but there were no differences in mortality or readmissions [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable and univariable Cox proportional hazards models were used to assess relative mortality. In addition, weighted regression models were obtained to estimate outcomes ( 17 , 18 ). Multivariable logistic regression was used to assess predictors of 60-day mortality.…”
Section: Methodsmentioning
confidence: 99%